Study on dehydrogenation and oxidation kinetics mechanisms of micron α-AlH3 in an oxidative atmosphere. (21st September 2020) - Li, Heping; Liang, Daolun; Yu, Minghui; Liu, Jianzhong; Wang, Yang; Pang, Aimin; Tang, Gen; Huang, Xuefeng
Abstract: Aluminum hydride (AlH3 ) exhibits attractive properties, such as high hydrogen/energy storage, relatively good stability, and low dehydrogenation temperature. Thus, AlH3 has appreciable prospects as a component in solid propellant for promoting the specific impulse of rocket engines and for effectively reducing the erosion of engine nozzles. The TG-MS, SEM, XRD, XPS, and EDS results show that the thermal reaction of AlH3 is divided into three stages: (1) Dehydrogenation (below 210 °C, 2AlH3 →2Al+3H2 ) starts from the inherent defects on the surface with an incomplete decomposition due to the passivation reaction in which an amorphous Al2 O3 layer is formed to encapsulate the contained hydrogen. This is accompanied by nucleation and growth of Al nuclei from the outer particles to the inner particles and the formation of H2 O via oxidation of the generated hydrogen. (2) The primary oxidation of Al (210–650 °C, 4Al+3O2 →2γ-Al2 O3 ) is attributed to a discontinuous layer of γ-Al2 O3, which is transformed from amorphous Al2 O3 that results in the reaction of naked residual Al and O2 . (3) The secondary oxidation of residual Al (above 650 °C, 4Al+3O2 →2α-Al2 O3 ) occurs because of the crystal conversion from γ-Al2 O3 to α-Al2 O3, which leads to the shrinkage of the oxide shell and to the formation of cracks. Also, melting of residual Al breaks the shell, and this induces further oxidation. The results obtained for the microscopic kinetics mechanisms of dehydrogenation and oxidation of AlH3, show a clear direction for research regarding modifications of AlH3 as the theoretical foundation and are beneficial for the wide use of AlH3 in applications such as solid propellant as an energetic material and as a hydrogen source for fuel cells. Highlights: Real-time mass and gaseous products were obtained during thermal reaction of AlH3 . Microscopic kinetics mechanism was studied via condensed products microstructure. Thermal reaction stages: dehydrogenation, primary oxidation, secondary oxidation. Clear direction shown to modify AlH3 as energetic material and hydrogen sources.